Tri Hita Karana Based Learning Videos on Social Science Lesson Content - I Wayan Agus Suwastina; Kadek Yudiana (Jurnal Ilmiah Sekolah Dasar, 2023)
Lack of learning media makes learning boring, and students lack awareness of problems surrounding each other and the environment. This research aims to create Tri Hita Karana-based learning video media by testing the feasibility, practicality, and effectiveness of the media used to improve student learning outcomes. This type of research is Research and Development with the ADDIE model. The subjects of this research were 3 experts, namely media experts, learning design experts and learning content experts to assess the suitability of the media, 1 teacher, and 27 grade V elementary school students involved in the practicality test and effectiveness test. The trial design used in this research is a pre-test and post-test design. The data collection methods used were questionnaires, observations and tests. The data analysis technique used is quantitative descriptive analysis. The research results show that the feasibility index for media experts and material testing is very good, and learning design experts are in a good category. The results of individual practicality tests, small group tests and student response tests are very good. The results of hypothesis testing on learning video media were declared effective in improving the learning outcomes of fifth-grade elementary school students. This research concludes that the media developed is feasible, practical and effective in improving student learning outcomes in social studies learning content.